2007
DOI: 10.3998/ark.5550190.0008.205
|View full text |Cite
|
Sign up to set email alerts
|

Calixarenes as sensor materials for recognition and separation of metal ions

Abstract: Chemical separation and speciation are two fundamental processes that have ushered significant advances in biological and material world. The underlying principles for most innovative separations involve molecular recognition and its subsequent translation to methodologies for detection and separation. Recent advances in the field have demonstrated that calix[n]arenes are attractive sensor materials for recognition of metal ions and small molecules and they can be employed for designing novel molecular filters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 3 publications
(3 reference statements)
1
36
1
Order By: Relevance
“…The calixarenes belong to cavity-shaped cyclic compounds which are broadly applied in a supramolecular recognition process as host molecules [ 17 , 18 ]. A number of studies relating to the calixarenes and their derivatives have shown that they are very sensitive, and selective recognition elements in electrochemical sensors are destined for metal ions determination [ 19 , 20 ]. The calixarenes-based sensors are also suitable for the determination of small biomolecules [ 18 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The calixarenes belong to cavity-shaped cyclic compounds which are broadly applied in a supramolecular recognition process as host molecules [ 17 , 18 ]. A number of studies relating to the calixarenes and their derivatives have shown that they are very sensitive, and selective recognition elements in electrochemical sensors are destined for metal ions determination [ 19 , 20 ]. The calixarenes-based sensors are also suitable for the determination of small biomolecules [ 18 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic ionophores as cyclodextrines [12, 13], crown ethers [14], and calixarenes/ calixresorcinarenes [2, 10, 11, 15–19] are effectively employed as surface modifiers and selective sensing platforms. Calix‐ionophores, due to their distinctive host‐guest interactions, selective capabilities, and amphiphilic character are broadly used in sensing networks [17, 20–24].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these functional groups can be modified to produce ionophores that are selective about compounds or metal ions [2] [3] [4]. For example, modification of the t-butyl group over the annular ring with a tetramer or hexamer group produces an ionophore that is selective to the cations of Rb, Sr, Cs, alkali metals, and alkaline earth metals [5].…”
Section: Introductionmentioning
confidence: 99%
“…
Research on the synthesis of the BCAC4ND2 ionophore from p-t-butylcalix [4]arene ethylester has been carried out. This study aims to synthesize the BCAC4ND2 ionophor from p-t-butylcalix[4]arene ethylester.
…”
mentioning
confidence: 99%
See 1 more Smart Citation